NEW PERSPECTIVES FOR TEACHING DENTISTRY - Santos, Alice Pereira da Costa; Rosa, Beatriz Salomão Porto-Alegre; Visconti, Maria Augusta (Revista Científica do CRO-RJ (Rio de Janeiro Dental Journal), 2020)
Higher education is challenged to think about how to enable people, at any stage of their lives, to take part in stimulating learning experiences. In this context, information and communication technology (ICTs) has been transforming a large part of society and there is little reason to believe that it will not be the definitive transformative innovation for higher education in the 21st century. Technology can help education to meet the expectations of better quality, while saving costs in an era of reduced funding and many political impasses facing educational issues in many countries.1 In March 2020, the COVID-19 pandemic demanded the immediate closure of face-to-face dental education to comply with social isolation standards, bearing in mind that clinical activity in dentistry occupies a unique place among those with the greatest potential for spreading the infection. Many dental schools faced the challenge of effectively involving students through virtual learning.2